2016
DOI: 10.1002/advs.201600060
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Oxide and Cobalt‐Graphitic Carbon Core–Shell Based Catalysts with Remarkably High Oxygen Reduction Reaction Activity

Abstract: The vital role of ethylenediaminetetraacetic acid on the structure and the oxygen reduction reaction activity of the non‐precious‐metal‐based pyrolyzed catalyst is reported and elaborated. The resultant catalyst can overtake the performance of commercial Pt/C catalyst in an alkaline medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(69 citation statements)
references
References 58 publications
(20 reference statements)
2
67
0
Order By: Relevance
“…[19] Our previous report demonstrated that ethylenediaminetetraacetic acid (EDTA) can promote the encapsulation process of the core by graphitic carbon. [20] Thus, to furthera ssociate the thickness of the carbon shell with HER activity,E DTAw as added to the precursors,a nd the corresponding pyrolysis products, denoted Ru 0.25 Co 0.75 P@NPC-EDTA, exhibited poor HER activity relative to Ru 0.25 Co 0.75 P@NPC, which mayh ave resulted from the thick carbon coats that were revealed by HRTEM in Figure S19 (Sup-portingI nformation). At hick carbon shell may block the active metal sites, caused lesse lectron transport, and thus reduced the catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…[19] Our previous report demonstrated that ethylenediaminetetraacetic acid (EDTA) can promote the encapsulation process of the core by graphitic carbon. [20] Thus, to furthera ssociate the thickness of the carbon shell with HER activity,E DTAw as added to the precursors,a nd the corresponding pyrolysis products, denoted Ru 0.25 Co 0.75 P@NPC-EDTA, exhibited poor HER activity relative to Ru 0.25 Co 0.75 P@NPC, which mayh ave resulted from the thick carbon coats that were revealed by HRTEM in Figure S19 (Sup-portingI nformation). At hick carbon shell may block the active metal sites, caused lesse lectron transport, and thus reduced the catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…All potentials were referred to the reversible hydrogen electrode (RHE) according to the following equation [Eq. (3)]: trueE4pt(RHE)=E4pt(Ag/AgCl4pt(Sat.4ptKCl)+0.1970.166667emnormalV+0.0590.166667empH …”
Section: Discussionmentioning
confidence: 99%
“…3a) was measured using the same ferro-ferricyanide oxidation-reduction system. Cobalt oxide Co 3 O 4 , as well-known material for its electrocatalytic activity [6,8,13,[33][34][35] in oxygen evolution reaction, was obtained during heat treatment of as-deposited Co(OH) 2 coatings at 673 K for 1 h. The lamellar structure and composition of tricobalt tetraoxide was confirmed in previous studies [23] by XRD, FTIR and XPS. In order to investigate the effect of temperature treatment to electroactive surface area, the same measurements as with Co(OH) 2 were performed (Fig.…”
Section: Determination Of Electroactive Surface Areamentioning
confidence: 53%